The study and fabrication of a novel thermally responsive microcarrier for cell culture application - Chou, Pui May (2016)
During conventional microcarrier cell culturing, the use of harmful trypsin or a mechanical scrapper during cell harvesting can damage the cell membranes and reduce cell yield. The development of a non-invasive harvestment process for cells is essential, for preserving cell functions and improving cell yield. The ultimate objective of the present study was to synthesize a novel polyNIPAm thermoresponsive microcarrier, to eliminate the use of trypsin or scrapper approaches for cell harvestment. Comprehensive investigation of processing parameters, of initiator type, surfactant composition, comonomer ratio, stirring rate and cross-linker content were performed, to gain improved understanding of the process-structure-property relationship, and thereby identify optimum processing conditions. PolyNIPAm microspheres possessing different size ranges and surface properties were synthesised successfully via suspension polymerisation. The use of different initiator types affected the polymerisation temperature, size and surface charge of the polyNIPAm product. The surface charge of the polyNIPAm microspheres was controlled by adjusting the surfactant composition. Copolymerisation with butyl methacrylate (BMA) improved the surface hydrophobicity of the microspheres for enhanced protein adsorption. Relatively small microspheres of diameters ~ 30 µm were formed when a high stirring rate of 400 rpm was used. It was found that the compressive modulus of the microspheres increased with increasing cross-linker content. In vitro cell trials were performed to appraise the cellular response to the polyNIPAm microspheres. The polyNIPAm microspheres were found to be biocompatible with human embryonic kidney (HEK) cells. Spontaneous cell detachment from the microspheres occurred upon lowering the incubation temperature of the culture media. The incorporation of 10 wt% of cetrylmethylammonium bromide (CTAB) surfactant and 30 wt% of BMA comonomer to the polyNIPAm exhibited a cell yield of ~ 1.7 x 106 cells/ml, which is comparable to commercial microcarriers (1.0 x 106 cells/ml).